The Lombard effect and other noise‐induced vocal modifications: insight from mammalian communication systems. (26th February 2013) - Hotchkin, Cara; Parks, Susan
ABSTRACT: Humans and non‐human mammals exhibit fundamentally similar vocal responses to increased noise, including increases in vocalization amplitude (the Lombard effect) and changes to spectral and temporal properties of vocalizations. Different research focuses have resulted in significant discrepancies in study methodologies and hypotheses among fields, leading to particular knowledge gaps and techniques specific to each field. This review compares and contrasts noise‐induced vocal modifications observed from human and non‐human mammals with reference to experimental design and the history of each field. Topics include the effects of communication motivation and subject‐specific characteristics on the acoustic parameters of vocalizations, examination of evidence for a proposed biomechanical linkage between the Lombard effect and other spectral and temporal modifications, and effects of noise on self‐communication signals (echolocation). Standardized terminology, cross‐taxa tests of hypotheses, and open areas for future research in each field are recommended. Findings indicate that more research is needed to evaluate linkages among vocal modifications, context dependencies, and the finer details of the Lombard effect during natural communication. Studies of non‐human mammals could benefit from applying the tightly controlled experimental designs developed in human research, while studies of human speech in noise should be expanded to include natural communicative contexts. The effects of experimental design and behavioural context on vocalizations should not be neglected as they may impact the magnitude and type of noise‐induced vocal modifications.